2020
DOI: 10.3389/fmed.2020.583031
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine Combined With Butorphanol or Sufentanil for the Prevention of Post-operative Nausea and Vomiting in Patients Undergoing Microvascular Decompression: A Randomized Controlled Trial

Abstract: Background: Patients undergoing microvascular decompression are often accompanied with high risk of post-operative nausea and vomiting (PONV). In this study, we compare the antiemetic efficacy of butorphanol or sufentanil combined with dexmedetomidine in patients undergoing microvascular decompression.Methods: Patients undergoing microvascular decompression were randomized into two groups. The primary outcome was the occurrence and severity of PONV during the 72 h after surgery. Secondary outcomes included lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…Butorphanol may also protect the myocardium [20] and help stabilize hemodynamic parameters [21], especially when administered with propofol [22]. Comparison of the effects of butorphanol with those of the opioid tramadol in women after receiving a cesarean section showed that butorphanol had significantly better analgesic activity as well as significantly lower risk of nausea, vomiting, dizziness, and 24-hour sedation after analgesia [23], leading to significantly higher patient satisfaction [24].…”
Section: Discussionmentioning
confidence: 99%
“…Butorphanol may also protect the myocardium [20] and help stabilize hemodynamic parameters [21], especially when administered with propofol [22]. Comparison of the effects of butorphanol with those of the opioid tramadol in women after receiving a cesarean section showed that butorphanol had significantly better analgesic activity as well as significantly lower risk of nausea, vomiting, dizziness, and 24-hour sedation after analgesia [23], leading to significantly higher patient satisfaction [24].…”
Section: Discussionmentioning
confidence: 99%
“…From the injured tissue, which results in peripheral sensitization and increases the pain effect. Substance P (SP) is a key factor in pain signal transduction, which plays a signal transduction role in nerve conduction [27] . Dexmedetomidine has an analgesic effect by inhibiting the release of substance P and other nociceptive substances from the presynaptic membrane of the descending medulla-spinal NE pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, surgical manipulation may predispose patients to PONV after MVD [ 21 ]. Several studies have been conducted to prevent PONV in patients undergoing MVD [ 23 , 25 ].…”
Section: Introductionmentioning
confidence: 99%